2016
DOI: 10.1080/1040841x.2016.1201041
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory mechanism of fungal elicitor-induced secondary metabolite biosynthesis in medical plants

Abstract: A wide range of external stress stimuli trigger plant cells to undergo complex network of reactions that ultimately lead to the synthesis and accumulation of secondary metabolites. Accumulation of such metabolites often occurs in plants subjected to stresses including various elicitors or signal molecules. Throughout evolution, endophytic fungi, an important constituent in the environment of medicinal plants have known to form long-term stable and mutually beneficial symbiosis with medicinal plants. The endoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 155 publications
0
80
0
2
Order By: Relevance
“…In this study, the effects of different fungal endophytes on the accumulation of alkaloids in L. radiata were quite different (Fig. 7); this may be because the mechanisms underlying the accumulation of secondary metabolites induced by fungal endophytes could depend on the endophyte and/or plant species (Zhai et al, 2017). Diverse fungal elicitors could be recognized by pattern recognition receptors on plant cell membranes and then different signalling cascades would be activated, which will further enhance secondary metabolite synthesis (Hao et al, 2010;Yuan et al, 2016b;Zhai et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study, the effects of different fungal endophytes on the accumulation of alkaloids in L. radiata were quite different (Fig. 7); this may be because the mechanisms underlying the accumulation of secondary metabolites induced by fungal endophytes could depend on the endophyte and/or plant species (Zhai et al, 2017). Diverse fungal elicitors could be recognized by pattern recognition receptors on plant cell membranes and then different signalling cascades would be activated, which will further enhance secondary metabolite synthesis (Hao et al, 2010;Yuan et al, 2016b;Zhai et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
“…7); this may be because the mechanisms underlying the accumulation of secondary metabolites induced by fungal endophytes could depend on the endophyte and/or plant species (Zhai et al, 2017). Diverse fungal elicitors could be recognized by pattern recognition receptors on plant cell membranes and then different signalling cascades would be activated, which will further enhance secondary metabolite synthesis (Hao et al, 2010;Yuan et al, 2016b;Zhai et al, 2017). Since we observed that some fungal endophytes promoted the accumulation of alkaloids, not only in the organ where they had been originally isolated but also in other organs of L. radiata (Table S3), the results indicate that the fungal colonization was involved in initiating certain long-distance signalling cascades, which later regulated the alkaloid synthesis in other locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, fungi are capable of producing different secondary metabolites such as antibiotics, volatile compounds and others, which is related to the activation of different metabolic pathways involving the biosynthetic precursors of these reactions (Zhai et al 2017; Alberti et al 2017). In G. can , the levels of histidine and xanthine, the main precursor metabolites in the biosynthesis of secondary metabolites, were elevated.…”
Section: Discussionmentioning
confidence: 99%
“…There are already many reports focusing on the crosstalk among ET, JA and SA signalling pathways, but the knowledge about crosstalk among these plant hormones in G. lucidum is very limited [57]. Therefore, more research about hormonal crosstalk in G. lucidum might open up perspectives to manipulate the biosynthesis of GA.…”
Section: Phytohormonesmentioning
confidence: 99%